Chapter Architettura e neuroscienze: una doppia elica - Eberhard, John Paul (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
The founder of the Academy of Neuroscience for Architecture relates the story of its in-spiration in Jonas Salk's insistence that his experience at the Abbey at Assissi helped him develop the vaccine for polio. He discusses the Golden Mean, children's perceptual houses and optogenics, as well as the importance of designing incubators and neonatal intensive care units according to the developmental needs of infants, rather than the convenience of the medical staff, and open awareness as a creative approach to problem solving.